ITSN1 and Ruk/CIN85 colocalized to clathrin-coated pits in MCF-7 cells - Nikolaienko, O.V.; Skrypkina, I.Ya.; Tsyba, L.O.; Drobot, L.B.; Rynditch, A.V. (Вiopolymers and Cell, 2009)
Activation of receptor tyrosine kinases (RTK) by corresponding ligands results not only in signal propagation, but also initiates a number of processes, such as clathrin-mediated endocytosis, which precisely regulate biological outcome. These processes are tightly controlled by coordinated action of a plethora of proteins – enzymes, scaffolds and inhibitory molecules. An example of an endocytic accessory protein that also functions in cell signaling is provided by intersectin 1 (ITSN1). Previously we have shown that ITSN1 forms a complex with adaptor protein Ruk/CIN85 and ubiquitin ligase Cbl-b, which are implicated in down regulation of RTK. The present study aimed to determine the subcellular localization of ITSN1-Ruk/CIN85 complexes relatively to clathrin light chain and Cbl-b. Methods. Transient transfection of MCF-7 breast adenocarcinoma cells with the constructs containing Omni-tagged intersectin 1 and clathrin light chain fused with mCherry fluorescent protein was utilized to determine subcellular localization by direct or indirect immunofluorescence. Results. We found that Ruk/CIN85-ITSN1 complexes partially colocalized with Cbl-b and clathrin light chain in MCF-7 cells. Conclusions. In our report we provide experimental evidence that ITSN1-Ruk/CIN85 complexes exist in pre-assembled state with Cbl-b and are targeted to clathrin-coated pits in MCF-7 cells. Активация рецепторних тирозин киназ соответствующими лигандами приводит не только к распространению сигнала, но и инициирует разные процессы, например, клатрин-опосредованный эндоцитоз, которые регулируют клеточный ответ. Эти процессы строго контролируются благодаря координированному действию большого количества белков – ферментов, адапторов и ингибиторов. Примером адапторного белка, функционирующего как в эндоцитозе, так и в клеточной сигнализации, служит интерсектин 1 (ITSN1). Ранее нами показано, что ITSN1 формирует комплекс с адапторным белком Ruk/CIN85 и убиквитин лигазой Cbl-b, участвующими в негативной регуляции рецепторных тирозинкиназ. Целью данной работы было выявление субклеточной локализации комплексов Ruk/CIN85-ITSN1 по отношению к клатрину и Cbl-b. Методы. Для определения локализации белков клетки аденокарциномы молочной железы человека MCF-7 транзиентно трансфицировали конструкциями, кодирующими ITSN1 и клатрин, и исследовали методами прямого и не прямого иммунофлуоресцентного анализа. Результаты. Показано, что ITSN1 и Ruk/CIN85 частично колокализуются с Cbl-b и клатрином в клетках линии MCF-7. Выводы. Установлено, что комплексы ITSN1 и белка Ruk/CIN85 частично колокализуются с Cbl-b и находятся в клатрин-окаймленных ямках клеток линии MCF-7 Активація рецепторних тирозинкіназ відповідними лігандами призводить не лише до розповсюдження сигналу, але й ініціює різні процеси, серед яких клатрин-опосередкований ендоцитоз, що регулюють клітинну відповідь. Такі процеси чітко контролюються завдяки координованій дії великої кількості білків ферментів, адапторів та інгібіторів. Прикладом адапторного білка, що функціонує як в ендоцитозі, так і в клітинній сигналізації, є інтерсектин 1 (ITSN1). У попередніх дослідженнях ми показали, що ITSN1 утворює комплекс з адапторним білком Ruk/CIN85 та убіквітинлігазою Cbl-b, які залучені до негативної регуляції рецепторних тирозинкіназ. Метою даної роботи було визначи ти субклітинну локалізацію комплексів Ruk/CIN85-ITSN1 по відношенню до клатрину та Cbl-b. Методи. Для встановлення локалізації білків клітини аденокарциноми молочної залози людини MCF-7 транзієнтно трансфікували конструкціями, що містять ITSN1 і клатрин, та вивчали методами прямого і не прямого імунофлуоресцентного аналізу. Результати. Показано, що ITSN1 і Ruk/CIN85 частковоко локалізуються з Cbl-b і клатрином у клітинах лінії MCF-7. Висновки. Продемонстровано, що комплекси Ruk/ CIN85 з ITSN1 колокалізуються з Cbl-b і знаходяться у клатрин-облямованих ямках клітин лінії MCF-7.